2015
DOI: 10.1039/c4fd00230j
|View full text |Cite
|
Sign up to set email alerts
|

Measuring induction times and crystal nucleation rates

Abstract: The Strathprints institutional repository (https://strathprints.strath.ac.uk) is a digital archive of University of Strathclyde research outputs. It has been developed to disseminate open access research outputs, expose data about those outputs, and enable the management and persistent access to Strathclyde's intellectual output. A large variation is observed in induction times measured under equal 5 conditions in 1 ml solutions. Ruling out experimental errors, this variation originates from the nucleation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 16 publications
4
161
1
1
Order By: Relevance
“…In contrast, the polymorphic outcome from a similarly supersaturated solution in DMF was shown to be seed‐dependent (Table ; XRPD results are shown in the Supporting Information), whereas unseeded solutions in DMF exhibited long induction times (up to 3 h) and spontaneously produced the RI form. In terms of kinetics of spontaneous nucleation, it has recently been reported that the nucleation rate of ssRII from unseeded IPA solution at β =3 ( J =668.0 m −3 s −1 ) is approximately 18 times higher than that of RI in unseeded DMF ( J =35.7 m −3 s −1 , at the same supersaturation) …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the polymorphic outcome from a similarly supersaturated solution in DMF was shown to be seed‐dependent (Table ; XRPD results are shown in the Supporting Information), whereas unseeded solutions in DMF exhibited long induction times (up to 3 h) and spontaneously produced the RI form. In terms of kinetics of spontaneous nucleation, it has recently been reported that the nucleation rate of ssRII from unseeded IPA solution at β =3 ( J =668.0 m −3 s −1 ) is approximately 18 times higher than that of RI in unseeded DMF ( J =35.7 m −3 s −1 , at the same supersaturation) …”
Section: Resultsmentioning
confidence: 99%
“…As the induction time can be experimentally determined by the isothermal method at a constant supersaturation level, the induction time data are frequently used as a measure of the nucleation event to calculate the interfacial energy of the crystallized substance in the literature [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…III E. Because NaCl solution droplets require time t ind (induction time) to adjust to the humidity inside the trap and thus reach the efflorescence concentration, the time t in Equations (1)-(2b) has to be replaced with t t ind . 55,56 The induction time becomes a fitting parameter and can be derived from fitting the experimental data. The fitting parameters and curves for all temperature settings examined in this study are given in the supplementary material together with the overview of experimental conditions.…”
Section: Efflorescence Nucleation Rate Of Nacl Solution Dropletsmentioning
confidence: 99%